Transposing Time: On the Artistic Methods of Transfurist Poets - Patsey, Anastasiia V. (Actual Problems of Theory and History of Art, 2020)
The heritage of the Transfurists — a group of artists and poets who united in the late 1970s around the ‘samizdat’ journal “Transponans” — is a unique example of how traditions of literature avantgarde of the first half of the 20th century can be set forward and reconsidered. The creative work of the transpoetsis based on the idea of translations, transposition of art works from one key into another. Using various instruments of experimental poetry and the principle of “recreation”, the Transfurists recycled literature works of the past engaging them with new meanings. The article describes the creative approach of the transfurist poets and presents the brief analysis of their artistic methods in the contemporary context.
Keywords: Transfurizm; avant-garde; experimental poetry; visual poetry; Transponans; Ry Nikonova; Sergey Sigey; nonconformism; samizdat